Unravelling the Immunity of Poultry Against the Extracellular Protozoan Parasite Histomonas meleagridis Is a Cornerstone for Vaccine Development: A Review - Mitra, Taniya; Kidane, Fana Alem; Hess, Michael; Liebhart, Dieter (Frontiers in Immunology, 2018)
The protozoan parasite Histomonas meleagridis is the causative agent of histomonosis in gallinaceous birds, predominantly in turkeys and chickens. Depending on the host species the outcome of the disease can be very severe with high mortality as observed in turkeys, whereas in chickens the mortality rates are generally lower. The disease is known for more than 100 years when in vitro and in vivo investigations started to understand histomonosis and the causative pathogen. For decades histomonosis could be well controlled by effective drugs for prevention and therapy until the withdrawal of such chemicals for reasons of consumer protection in Europe, the USA and additional countries worldwide. Consequently, research efforts also focused to find new strategies against the disease, resulting in the development of an efficacious live-attenuated vaccine. In addition to efficacy and safety several studies were performed to obtain a deeper understanding of the immune response of the host against H. meleagridis. It could be demonstrated that antibodies accumulate in different parts of the intestine of chickens following infection with H. meleagridis which was much pronounced in the ceca. Furthermore, expression profiles of various cytokines revealed that chickens mounted an effective cecal innate immune response during histomonosis compared to turkeys. Studying the cellular immune response following infection and/or vaccination of host birds showed a limitation of pronounced changes of B cells and T-cell subsets in vaccinated birds in comparison to non-protected birds. Additionally, numbers of lymphocytes including cytotoxic T cells increased in the ceca of diseased turkeys compared to infected chickens suggesting an immunopathological impact on disease pathogenesis. The identification of type 1 and type 2 T-helper (Th) cells in infected and lymphoid organs by in situ hybridization did not show a clear separation of Th cells during infection but revealed a coherence of an increase of interferon (IFN)-γ mRNA positive cells in ceca and protection. The present review not only summarizes the research performed on the immune response of host birds in the course of histomonosis but also highlights the specific features of H. meleagridis as a model organism to study immunological principles of an extracellular organism in birds.